PEMEROLEHAN BAHASA BAKU SHABIRA ALULA DALAM VIDEO TIKTOK SHABIRA ALULA DAN AYAH - Lutfiana Askuri Khoiri Nabela; Dian Risdiawati (Jurnal Ilmiah SEMANTIKA, 2023)
With the rise of language development in the era of globalization, this research is expected to be useful for others by adding knowledge and insight and being able to teach good language to children, by teaching good language to children can influence the development of children's attitudes and character. This research focuses on the acquisition of standard language on Shabira Alula and Ayah's TikTok, namely in the acquisition of language in the fields of phonology, syntax, and semantics. This study aims to explain and describe language acquisition in the fields of phonology, syntax, and semantics in Shabira Alula. This study uses a qualitative descriptive design with data collection techniques using observation techniques and also note taking. The results of this study indicate that Shabira Alula has been able to pronounce standard words as a whole or only in the form of words, and has been able to pronounce vowel and consonant phonemes quite well, but Shabira Alula is not perfect in pronouncing phonemes [r]. In acquiring syntax, Shabira Alula has been able to obtain sentences from one-word, two-word and multi-word utterances. Apart from that, Shabira Alula's declarative, interrogative, imperative and interjection sentences have also been able to do this, although there are still many advantages and disadvantages in the perfection of her pronunciation. In semantic acquisition, Shabira Alula has been able to determine the context of the conversation so that the resulting response does not deviate from the conversation.